2009
DOI: 10.1017/s0022112009991078
|View full text |Cite
|
Sign up to set email alerts
|

Torque reduction in Taylor–Couette flows subject to an axial pressure gradient

Abstract: The paper investigates the phenomena occurring in a Taylor–Couette flow system subject to a steady axial pressure gradient in a small envelope of the Taylor–Reynolds state space under transitional regimes. A remarkable net power reduction necessary to simultaneously drive the two flows compared to that required to drive the Taylor–Couette flow alone is documented under non-trivial conditions. The energy transfer process characterizing the large-scale coherent structures is investigated by processing a set of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…What has not yet been considered is the effect of the axial pressure gradient, which has been shown in some cases to reduce the torque requirement (Manna and Vacca, 2009), although the Taylor numbers in the present study are much higher than covered by Manna and Vacca thus the observed torque reduction is unlikely to manifest here. A formula for the effect of axial pressure gradient on friction torque was developed by Yamada (1962) although it is based on the axial Reynolds number which is not known in the present work and consequently cannot be used to improve the torque estimation.…”
Section: Steady State Simulation Methodsmentioning
confidence: 51%
“…What has not yet been considered is the effect of the axial pressure gradient, which has been shown in some cases to reduce the torque requirement (Manna and Vacca, 2009), although the Taylor numbers in the present study are much higher than covered by Manna and Vacca thus the observed torque reduction is unlikely to manifest here. A formula for the effect of axial pressure gradient on friction torque was developed by Yamada (1962) although it is based on the axial Reynolds number which is not known in the present work and consequently cannot be used to improve the torque estimation.…”
Section: Steady State Simulation Methodsmentioning
confidence: 51%
“…This reduction in plume ejection results in a reduced transport of angular velocity (torque). A similar reduction in the torque caused by a mean flow was also seen when forcing the flow with an axial pressure gradient by Manna & Vacca (2009). Vortices with a smaller wavelength have smaller wind-sheared regions and thus result in a larger N u ω , if this suppression is taking place.…”
Section: Dependence On Number and Size Of Rollsmentioning
confidence: 56%
“…Shear stresses relative to TCN1 are significantly lower than the one associated with TCN2 both for intact and etched fiber. Except the axial pressure gradient due to gravity (equal in the two cases), there are no other external axial pressure gradients acting on the system that can induce torque reductions [21]. Differences on shear stresses are only ascribable to the different rotation regimes.…”
Section: Variation Of Flow Regimes For Tcn1 and Tcn2 Due To Fiber Etcmentioning
confidence: 99%